2019
DOI: 10.1021/acsomega.8b03031
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Predominant Substitutional Bonding Environment in B-Doped Single-Walled Carbon Nanotubes

Abstract: B-doped single-walled carbon nanotubes have been synthesized from sodium tetraphenyl borate and record incorporation percentages of B heteroatoms have been found in this material as-synthesized. However, carbonaceous impurities, besides other byproducts, can still contain boron and therefore exhibit various types of competing bonding environments. To circumvent this issue, which has constantly hindered a conclusive insight to the existing bonding environments in materials alike, we have employed a purification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Boron doping in carbon nanotubes has been achieved by in situ doping during laser ablation, arc discharge, and chemical vapor deposition (CVD) or by after-synthesis doping using postsubstitution reaction . Incorporation rates of substitutional boron in SWCNT lattices are in general low (<1 atom %), , and efforts in this field are being made to increase the boron dopant concentration. , Boron-doped single-walled carbon nanotubes (B-SWNTs) can be produced in significant amounts, which is advantageous for the potential TE applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boron doping in carbon nanotubes has been achieved by in situ doping during laser ablation, arc discharge, and chemical vapor deposition (CVD) or by after-synthesis doping using postsubstitution reaction . Incorporation rates of substitutional boron in SWCNT lattices are in general low (<1 atom %), , and efforts in this field are being made to increase the boron dopant concentration. , Boron-doped single-walled carbon nanotubes (B-SWNTs) can be produced in significant amounts, which is advantageous for the potential TE applications.…”
Section: Introductionmentioning
confidence: 99%
“…Boron doping in carbon nanotubes has been achieved by in situ doping during laser ablation, arc discharge, and chemical vapor deposition (CVD) or by after-synthesis doping using postsubstitution reaction . Incorporation rates of substitutional boron in SWCNT lattices are in general low (<1 atom %), , and efforts in this field are being made to increase the boron dopant concentration. , Boron-doped single-walled carbon nanotubes (B-SWNTs) can be produced in significant amounts, which is advantageous for the potential TE applications. So a pioneer study has reported increased Seebeck coefficient, S , values for CVD produced B-SWCNTs compared to those for pristine SWCNTs .…”
Section: Introductionmentioning
confidence: 99%
“…The transparent conduction of electrodes is important to photoelectronic devices, such as solar cells and photodetectors. Commercial transparent conducting oxides, such as indium-tin oxide [221] and fluorine-doped tin oxide [222], are predominantly n-type doping due to oxygen vacancies. The limitation for transporting electrons does not satisfy the hole transport requirement for collecting generated solar absorber materials.…”
Section: Photoluminescence For Dna Sensingmentioning
confidence: 99%
“…[43,44] Unlike chemical doping, in this method, the boron atoms are stable after entering the carbon nanotube lattice, and the dopants interact covalently with the host atoms, exhibiting a strong capacity to modify the electronic properties of carbon nanotubes, and the resulting doped carbon tubes will have a high degree of structural stability. [45,46] At this stage, boron-doped carbon tubes are mainly doped in situ by laser ablation, [47] arc discharge, [48] and chemical vapor deposition (CVD) [49,50] or by synthesis through postreaction. [51] For the substitution reaction of CNTs B x C 1Àx , the following chemical reactions have been previously proposed…”
Section: Introductionmentioning
confidence: 99%
“…The doping rate of substituted boron in the carbon nanotube lattice is usually low, and efforts are underway to increase the boron doping concentration in this field. [49,50] B-CNTs can be prepared in large quantities, and this is advantageous for potential TE applications. During this period, thermoelectric properties were improved by boron doping of CNTs.…”
Section: Introductionmentioning
confidence: 99%